Promoting the private sector for employment and poverty reduction - a central task of development cooperation - Tilman Altenburg (Deutsches Institut für Entwicklungspolitik (DIE), 2000)
The last two decades have experienced hardly any improvement in the indicators for employment and poverty in the developing countries. Progress can be made only with an economic policy that creates the conditions required for economic growth centered on the private sector and at the same time seeks to facilitate the participation of insufficiently integrated population groups in techno-organizational learning processes and their functional incorporation in differentiated, specialized, and competitive economic sectors.Economic growth creates jobs, unless growth rates are so low that they are cancelled out by growth in productivity. Growth also benefits the poor, whose incomes normally rise in parallel to economic growth rates. However, growth does not automatically contribute to overcoming the segmentation of labor markets, raising the productivity of the informal sector, and incorporating it into the modern sector of a national economy. What is called for are therefore concepts aimed at a more inclusive pattern of growth.Under the conditions of increasingly open markets, sustainable economic growth can be achieved only by a competitive private sector. For this reason alone there is no goal conflict between a competitive orientation, full employment, and poverty reduction. Moreover, the world's highly developed economies show that small enterprises can ensure national competitiveness and innovativeness while at the same time creating jobs. This does, however, presuppose that the businesses in question focus on complementary tasks in the production systems, be it as specialized service providers, component manufacturers, or providers of niche products.Without promotion of the private sector development cooperation will be unable to fulfill sustainably its task of reducing poverty in its partner countries. It would, however, be wrong to assume, as is often done, that economic promotion achieves its optimal poverty-reducing impacts when it is brought to bear directly on traditional smallbusiness activities engaged in by poor target groups. Most of these activities hold out few prospects for further development. Greater, and above all more sustainable, employment and poverty effects can be reached if promotion of the private sector helps given branches of industry to cope with the ongoing process of structural change by encouraging company-level competitiveness and the development of efficient forms of intercompany specialization.Development cooperation can better contribute to improving the framework needed for economic growth by more consistently keying funds to the criteria set out by the German Ministry for Economic Cooperation and Development (BMZ) for framework conditions conducive to development as well as by according high priority to high-level advisory assistance. In addition, it would be important to gear economic promotion to medium-sized businesses that hold out promise for the future, e.g. service providers in the fields of IT and logistics, suppliers, and exporters whose innovation and specialization generate positive externalities for the national system of production and services.
Keywords: 330